2022
DOI: 10.18280/ijsdp.170422
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Poverty, Unemployment, Economic Growth, and Investment in West Sumatra Province

Abstract: This research aims to analyze the relationship between poverty, unemployment, investment, and economic growth in a simultaneous equation system with the factors that influence them. This condition is essential to identify the causes of poverty and unemployment and how investment and economic growth play a role in overcoming these problems. This research uses panel data from 19 districts/cities in West Sumatra from 2015 to 2020. The estimation technique used is a simultaneous equation using several classical as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Because to be able to get the same goods or services, they have to pay more, which will have an impact on the decline in people's welfare which will result in a decrease in EG. The results of this study are consistent with the direction of influence between INF on EG that has been carried out by previous researchers [34,35], who found that INF would reduce EG.…”
Section: Analysis Modelsupporting
confidence: 93%
“…Because to be able to get the same goods or services, they have to pay more, which will have an impact on the decline in people's welfare which will result in a decrease in EG. The results of this study are consistent with the direction of influence between INF on EG that has been carried out by previous researchers [34,35], who found that INF would reduce EG.…”
Section: Analysis Modelsupporting
confidence: 93%
“…There are low standard deviations and small interquartile ranges on these causes. Therefore, all experts agree that some causes, such as the absence of job vacancies in home country, poverty, economic prospects, language similarity with the home country, distance to the destination country, and living costs in the destination country, are factors causing international labor migration [41,42]. Some causes, such as the absence of vacancies in the home country, poverty, poor economic prospects in the home country, and language similarity boost international labor migration.…”
Section: Discussionmentioning
confidence: 97%
“…This research uses a quantitative descriptive method. This descriptive method is used to investigate the value of a variable independently, either one or more variables, without create comparisons or linking between variables [19].…”
Section: Methodsmentioning
confidence: 99%